Development and validation of integrative Islamic personality inventory among youth in Turkey - Tekke, Mustafa
Islamic personality is the manifestation of Tawhidic paradigm in particular way of Prophet Muhammad (SAW) express his individual traits or adapts to diverse situations in the world, manifested aspects of a personal self, life definition and view that are guided by teaching of Qur'an and motivated by belief. Some of the most important values that form the core of this personality are Tawhid, Nubuwwa, and Self. In this study, the three subject matters have been selected to compose a tool of assessment which is called the Integrative Islamic Personality Inventory. Many tests have been developed with a Muslim population based on their culture and paradigms. The present study is an attempt to produce a new model based on integration of Western and Islamic paradigm. The Integrative Islamic Personality Inventory was developed within a specific framework in order to assess the self-introspection and self- improvement. With this idea of integrative Islamic personality, a Muslim individual is able to identify the area where improvements could be made because of Muslim's concern. This research was conducted at the ten universities in West and East of Turkey. The sample size was 1235. The instrument has been devised and validated through a scientific method to ensure its reliability and validity. Cronbach's alpha was used to test its reliability. Two advanced statistical methods were used, namely the Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA). EFA was used to identify the underlying dimensions for each construct of the instrument. CFA was used to confirm the dimensions and to analyse the fitness of the collected data in the hypothesized model. The results provide evidence that the developed instrument achieved sound psychometric properties. The reliability test indicated that the instrument was reliable given the overall reliability value of Cronbach's Alpha was .963. The findings revealed that with the use of EFA, Tawhid construct produced 5 items, Nubuwwa construct generated 5 items and Self containing Self-striving, Self-regard, and Self-neglect constructs, each produced 3 items. The CFA results showed that the goodness-of-fit indices for the revised model were as follows: CMIN/DF=3.258; GFI=.961; CFI=.955; TLI=.946 and RMSEA=.043; each of the indices was above the threshold values. In conclusion, this study has produced a prototype of the Integrative Islamic Personality Inventory which achieved sound psychometric properties and contributed to the development of a novel psychological instrument from the Western and Islamic perspective.